THE ROLE OF THE STUDENT TEACHER MUSYAWARAH (MGMP) IN IMPROVING THE UNDERSTANDING OF PKN TEACHERS ABOUT HUMAN RIGHTS (HAM) - Aries Abbas; Marhamah Marhamah (Ri'ayah: Jurnal Sosial dan Keagamaan, 2020)
Respecting children's views is a fundamental principle that relates to all aspects of the implementation and interpretation of other articles of the convention. Every child's views need to be considered in making decisions that will affect the child's life and development. Factors that can affect the understanding of Civics teachers, the existence of socialization with fellow Civics teachers, the existence of a two-way communication with MGMP members, the existence of shared perceptions in overcoming problematic students, the existence of collaboration when solving problems faced by students and cooperation can be carried out with teachers PAI, counseling teachers, Civics teachers must know or really understand the role and objectives of Civics learning, because Civics subjects have a role in education to develop character development through the role of Civics teachers. In accordance with one of the missions of the new paradigm Civics subject, namely as character education. Civics as one of the subjects that have content in moral education and nationalism, is a subject that is obliged to take part in the character education process through the role of Civics teachers. By applying appropriate teaching methods and supported by all levels of personnel at these educational institutions, Civics teachers can take the initiative to be the driving force for the character learning program. As the output of this Civics learning, there will be a generation with truly quality human resources in accordance with the goals of national education.